Answer :

Let the two zeroes be a and b.

The generalized form of the quadratic equation with sum and product of zeroes a and b is as follows:

ax^{2} + bx + c = 0 ………………… (i)

Now in this case

∴ a + b = -b/a = -3

∴ ab = c / a = 2

If a = k where k is any real number

b = 3k ………………… (ii)

c = 2k ………………… (iii)

Put values from (ii) and (iii) in (i)

kx^{2} + 3kx + 2k = 0

k (x^{2} + 3x + 2) = 0

Therefore the quadratic equation is as follows:

x^{2} + 3x + 2 = 0

Rate this question :

If u(x) = (x – 1)Rajasthan Board Mathematics

Find the lowest cRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics

The area of a recRajasthan Board Mathematics

The LCM and HCF oRajasthan Board Mathematics

If α and β are thRajasthan Board Mathematics

Find the zeroes oRajasthan Board Mathematics

Write ShridharachRajasthan Board Mathematics

Solve the followiRajasthan Board Mathematics